Self-employed professionals in the European labour market. A comparison between Italy, Germany and the UK. (November 2018) - Borghi, Paolo; Mori, Anna; Semenza, Renata
The transition to an on-demand service economy, supported by unprecedented technological developments and the digital revolution, has modified traditional self-employed professions and generated new ones, fostering the growth of a body of highly qualified and hyper-specialised self-employed professionals in the European economies. An analysis of this phenomenon highlights three critical questions, connected to their position in the labour market: 1) the contested definition of their legal status and the (ad hoc) regulation adopted; 2) their position within each national social protection system; 3) the complexity of collective representation in a context of major labour market fragmentation. The article explores these issues from a socio-economic perspective, comparing three European countries − Italy, Germany and the UK − with different welfare state regimes and diverse models for regulating professions. First findings show partly divergent responses to such common challenges, yet display some positive signs of change for self-employed professionals.